Staphylococcal Enterotoxin O Exhibits Cell Cycle Modulating Activity - Hodille, Elisabeth; Alekseeva, Ludmila; Berkova, Nadia; Serrier, Asma; Badiou, Cedric; Gilquin, Benoit; Brun, Virginie; Vandenesch, François; Terman, David S.; Lina, Gerard (Frontiers in Microbiology, 2016)
Maintenance of an intact epithelial barrier constitutes a pivotal defense mechanism against infections. Staphylococcus aureus is a versatile pathogen that produces multiple factors including exotoxins that promote tissue alteration. The aim of the present study is to investigate the cytopathic effect of staphylococcal exotoxins SEA, SEG, SEI, SElM, SElN and SElO on the cell cycle of various human cell lines. Among all tested exotoxins only SEIO inhibited the proliferation of a broad panel of human tumor cell lines in vitro. Evaluation of a LDH release and a DNA fragmentation of host cells exposed to SEIO revealed that the toxin does not induce necrosis nor apoptosis. Analysis of the DNA content of tumor cells synchronized by serum starvation after exposure to SEIO showed G0/G1 cell cycle delay. The cell cycle modulating feature of SEIO was confirmed by the flow cytometry analysis of synchronized cells exposed to supernatants of isogenic S. aureus strains wherein only supernatant of the SElO producing strain induced G0/G1 phase delay. The results of yeast-two-hybrid analysis indicated that SEIO potential partner is cullin-3, involved in the transition from G1 to S phase. In conclusion, we provide evidence that SEIO inhibits cell proliferation without inducing cell death, by delaying the host cell entry into the G0/G1 phase of the cell cycle. We speculate that this unique cell cycle modulating feature of this toxin allows SEIO producing bacteria to gain an advantage in arresting the cell cycle of target cells as part of a broader invasive strategy.